Citizen experience towards humanizing digital government: a case in Malaysia - Hussein, Idyawati; Mat, Turidi; Mahmud, Murni; Ab Razak, Rosida (ACM, 2017)
ABSTRACT This paper identifies citizens’ experience in an ideation sampling is applied to find subjects willing to participate on a particular date and able to explain their experiences in this domain in a reflective manner. This platform provides potential creative solutions to the problems. A sprint design method is adopted in order to produce an impactful outcome to the participatory approach.